PERTUMBUHAN DAN PRODUKSI BAWANG MERAH (Allium ascalonicum L.) DENGAN PEMBERIAN PUPUK KANDANG AYAM DAN EM4 (Effective Microorganisms4 - Ashrafida Rahmah; Rosita Sipayung; Toga Simanungkalit (Jurnal Agroekoteknologi, 2013)
Shallot is the one of leading vegetable which has long been cultivated by farmers intensive, the lowyields of shallot in Indonesia is caused by the use of low quality seeds and planting medium that isnot good. Efforts to increase onion yields, among others by chicken manure and EM4. Thisresearch has been conducted to obtain the optimal dose the effect of chicken manure and EM4application on the growth and yield of the shallot. Research was conducted on Jalan Pasar Satu,Medan Selayang, Medan with a height of 25 m above sea level on June to August 2012. usingrandomized block design of two factors, the factors are chicken manure (0, 40, 80, 120 g / plant) andEM4 (0, 3.5, 7 cc / l of water). The parameters observed were plant height, tillers number, leafnumber, wet weight per sample, wet weight per plot, dry weight per sample, dry weight per plot andclove number. The results showed that treatment of chicken manure significantly influenced all theparameters in which a dose of 120 g / plant showed the highest yields. EM4 treatment significantlyinfluenced the parameters of wet weight per plot and dry weight per plot. Interaction of bothtreatments significantly influenced wet weight per plot, dry weight per plot, and the cloves numberper sample.Key words : shallot, chicken manure, EM4